2018
DOI: 10.1017/s1049023x18001188
|View full text |Cite
|
Sign up to set email alerts
|

On the Way Out: An Analysis of Patient Transfers from Four Large-Scale North American Music Festivals Over Two Years

Abstract: IntroductionMusic festivals are globally attended events that bring together performers and fans for a defined period of time. These festivals often have on-site medical care to help reduce the impact on local health care systems. Historically, the literature suggests that patient transfers off-site are frequently related to complications of substance use. However, there is a gap in understanding why patients are transferred to hospital when an on-site medical team, capable of providing first aid services blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The aim of the interviews was to identify all the factors that the rescue authorities need to consider when they are preparing for mass gatherings. The interview structure was based on previous studies on mass gatherings [8,11,[13][14][15]23,25,37]. The original interview structure included background information and eight topics.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the interviews was to identify all the factors that the rescue authorities need to consider when they are preparing for mass gatherings. The interview structure was based on previous studies on mass gatherings [8,11,[13][14][15]23,25,37]. The original interview structure included background information and eight topics.…”
Section: Methodsmentioning
confidence: 99%
“…According to our results, multi-authority collaboration in the pre-event planning phase manifests, for example, as consultation of an EMS specialist regarding the planned attendee numbers, and the competence of the on-site medical care provided in the emergency plan. Previous studies showed that having medical professionals available among the first-aid providers and the use of treat-and-release directives have an impact on the need for transport to hospital, and in turn affect the workload for the EMS system and healthcare facilities [15,16,18,21,23]. According to an Australian study by Zeitz et al [8], the increase in workload for the rescue service in mass gatherings with a total of 5.7 million attendees in a two-year period, was only minor.…”
Section: Co-operation In the Pre-planning Phasementioning
confidence: 99%
See 2 more Smart Citations
“…This was evident with the 420 cases seen within the facility over the 7‐day period with only a small proportion (0.03%, 0.3/1000) requiring transfer by ambulance to the ED. As noted in other out‐of‐hospital ED avoidance strategies the multi‐disciplinary and inter‐agency staffing configuration likely contributed to this success; however, accompanying comprehensive structure and process evaluations of this and other EHS located at MGEs is required to understand this further. Additional public messaging to young adults attending Schoolies may be considered by event planners to create awareness of the EHS which may further minimise the impact on the ED …”
Section: Discussionmentioning
confidence: 99%